The Analysis Study of Prevalence of Chronic Kidney Disease in Patients with Chronic Obstructive Pulmonary Disease : A Comprehensive Systematic Review - Visgint, Aprima; Dwigint, Sabrine; Trigint, Dara Vanka (The International Journal of Medical Science and Health Research, 2024)
Background: The relationship between COPD and chronic kidney disease (CKD) is complex, with CKD often overlooked in older populations. The study aims to investigate the prevalence, risk factors, and impact of CKD on mortality and renal failure, highlighting the need for comprehensive health care. Methods: Following PRISMA 2020 guidelines, this systematic review focused exclusively on full-text articles published in English between 2011 and 2024. Result: The study conducted a comprehensive review of over 8,000 publications sourced from reputable databases, including ScienceDirect, SagePub, and PubMed. Following an initial screening, eight publications were identified as warranting more in-depth analysis. Consequently, a thorough review of these selected studies was performed to ensure a detailed and rigorous evaluation. Conclusion: CKD is a significant risk factor for COPD patients, with 15.6% diagnosed aged 40 and older. Common risk factors include advancing age, diabetes, hypertension, elevated BMI, and cigarette smoking. COPD is associated with systemic inflammation, contributing to conditions like diabetes, muscle wasting, and kidney disease. Proactive management approaches are needed to address renal implications.